Perbandingan Pengembangan Sistem Dengan Pendekatan Konvensional dan Low-Code Pada Sistem Pendukung Keputusan Penilaian Kinerja Pegawai - Carissa Maharani Chandra; Muhammad Rachmadi (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2024)
PT XYZ is a company engaged in the supply of materials, suppliers, and services, especially in the field of electrical equipment, such as generators, mechanical devices, electrical devices, cables, electricity meters, and so on. The company has a total of 26 employees, all of whom are permanent employees. This company has assessed employee performance every month, but it is done using narratives so it is still subjective and there is no ranking. This is certainly very difficult for HR staff in determining the best employees every month. The purpose of this Employee Performance Assessment Decision Support System design is to improve accuracy and efficiency in calculating employee performance to determine the best employees. In this research, the system development method used is the Rational Unified Process (RUP). This system development also uses two main approaches, which are low- code approach (OutSystems platform) and conventional approach (Laravel framework). From the development using the RUP method, it can develop a Decision Support System for Employee Performance Assessment for PT XYZ.